URGENSI APLIKASI PSIKOLOGI PENDIDIKAN TERHADAP PROSES BELAJAR MENGAJAR - I Made Ariasa Giri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The study of educational psychology in relation to the development of the education curriculum is mainly concerned with understanding aspects of behavior in the context of teaching and learning. It is undeniable that for a long time the field of educational psychology has been used as a foundation in the development of educational theory and practice and has made a major contribution to education, including the development of curriculum, learning systems and assessment systems. The role of the teacher in the teaching-learning process, the teacher not only appears again as a teacher (teacher), such as its prominent function so far, but instead switches as a coach (coach), counselor (counselor) and learning manager (learning manager). To achieve the main objectives of education, the role of educators should not only be oriented to academic values ??that are fulfilling cognitive aspects, but also oriented to how a student can learn from the environment from the experience and greatness of others, from the wealth of the vast expanse of nature, so with the establishment the duties and roles of teachers in the world of education, especially in teaching and learning activities are expected to be the teacher can know the duties and responsibilities as educators and is expected to establish a harmonious relationship with students so that the hope of achieving educational goals can be easily realized.